Edukasi dan Pemeriksaan Darah dalam Rangka Pencegahan Penyakit Tidak Menular - Margareta Haiti; Novita Anggraini; Victoria Ire Tominik (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
Non-communicable diseases (PTM) are a group of chronic diseases, not contagious and can attack all organs of the body, so PTM has a large impact both in terms of morbidity and mortality on public health. Based on information from community leaders from the Sukarami Village, many people experience hypertension, diabetes, rheumatism or pain in the joints so that people are very much expecting help from health workers to provide counseling and health checks in order to prevent disease or attempt to find the cause of the disease. Residents who attended the PKM activities amounted to 138 people. The results of glucose level examination obtained a normal category of 111 people, Prediabetes category as many as 21 people and diabetes category as many as 6 people while the examination of uric acid levels obtained normal results as many as 101 people, abnormal category as many as 36 people and not examined as many as 1 person but the results the measurement of people's blood pressure that came showed 67 (48.6%) more than normal meaning that quite a lot of people tended to suffer from hypertension. It was concluded that community awareness of the importance of checking blood sugar and gout, especially for those aged> 40 years, still needs to be improved through regular education and blood tests to prevent (preventive efforts), especially non-communicable diseases.